Rancangan Dan Implementasi Jaringan Hotspot Dengan Menggunakan Metode Queue Tree Pada Mikrotik Sebagai Penunjang Pembelajaran Online Di Desa Pasilian - Siti Safila Dewi; Ari Syaripudin (CV. Multi Kreasi Media, 2024)
Internet access is the ability of an individual or group to connect to the internet using a computer terminal or other device. Internet access in Pasilian Village is not yet available with many ISPs because ISP providers are still expensive there so that some parents of students in Pasilian Village cannot afford ISPs. Students still find it difficult to access the internet for free, in Pasilian Village there are no free hotspots. Here the authors will create free hotspots and cheap hotspots. The benefits before and after the existence of free hotspots and cheap hotspots are very clear for the lower middle class as well as for students and students to make it easier for them to access the internet and minimize the cost of hiring an expensive ISP in their surroundings. The advantage of using Queue Tree bandwidth management is being able to adjust the size of the bandwidth needed by the client so that the distribution of bandwidth to clients becomes regular, fair and can maximize the available bandwidth. Previous research by Cahyo Prihantoro, Agung Kharisma Hidayah, and Sandhy Fernandez (2021) conducted research with the title